Factors Favoring Long Term Survival in Patients with Stage IV Epithelial Ovarian Cancer: An Institutional Research - Sarwar, Hafiz Abubakar; Iftikhar, Jhanzeb; Yasmeen, Samia; Sheikh, Fareeha; Ali, Fatima; Syed, Aamir Ali; Siddiqui, Neelam (Asian Pacific Journal of Cancer Care, 2020)
Objective: Our aim was to identify factors favoring long term survival in patients presenting with stage IV epithelial ovarian cancer. Methods: We did retrospective analysis of thirty patients with stage IV epithelial ovarian cancer diagnosed and treated at Shaukat Khanum Memorial Cancer Hospital, Lahore, Pakistan from 2006 to 2013. Patient’s demographics, clinical data and histopathology were abstracted from cancer registry department of our hospital. Chi-square test was used to find the association between clinic-pathological variables and long term survival. Result: All patients received chemotherapy and surgery as per ovarian cancer guidelines. Of the thirty patients, eleven patients survived greater than four years median survival was recorded as thirty five months. Absence of co-morbidities and good performance status indicated good results of therapy however did not have statistically significant impact on survival. Higher CA-125 at presentation i.e.>1000(normal range : <21 U/ml), response to initial chemotherapy, interval cytoreductive surgery and complete response after induction therapy were significantly associated with long term survival (P<0.05). Conclusion: Prognosis of patients presenting with stage IV epithelial ovarian cancer remains poor. Very high values of CA-125 (>1000) at presentation, response to initial chemotherapy, interval surgical resection and complete remission after induction therapy, appear to be significant prognostic factors for long term survival. Further studies exploring molecular profiling and immunological factors are warranted.